2021
DOI: 10.1159/000515914
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Breast Fine-Needle Aspiration Biopsy Using the International Academy of Cytology Yokohama System in Clinico-Radiologically Indeterminate Lesions: Initial Findings Demonstrating Value in Lesions of Low Suspicion of Malignancy

Abstract: <b><i>Background:</i></b> Fine-needle aspiration biopsy (FNAB) in breast lesions offers accurate results in differentiating benign and malignant lesions. However, its role is unclear when core-needle biopsy (CNB) is available, the latter providing additional information regarding tumor grade, invasion, and hormone receptor status in malignant lesions. In benign breast lesions, especially in BIRADS category 4a and 4b, FNAB, and CNB provide similar pathological information, whereby FNAB m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition, more studies estimating the accuracy of the IAC System for papillary lesions [53,54], small size [55], and male sex [56] could be useful. Breast FNAB using rapid on site evaluation (ROSE) [7,14] or in populations with a lower risk such as a mammographic BIRADS 4a lesion [24], can diagnose a case as benign rapidly and economically, benefiting the patient by saving time, discomfort, and expense while effectively providing the same information as a core needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more studies estimating the accuracy of the IAC System for papillary lesions [53,54], small size [55], and male sex [56] could be useful. Breast FNAB using rapid on site evaluation (ROSE) [7,14] or in populations with a lower risk such as a mammographic BIRADS 4a lesion [24], can diagnose a case as benign rapidly and economically, benefiting the patient by saving time, discomfort, and expense while effectively providing the same information as a core needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…This IAC Yokohama System (IAC System) proposes a standardized format for reporting and includes a cytopathological category which is linked to a risk of malignancy (ROM). The IAC Yokohama system is an internationally authored development of several previous recommendations from the National Mammographic Breast Cancer Screening Program in Australia and the National Cancer Institute (NCI) of the USA After the IAC System was published, it was quickly followed by multiple studies using the system that have demonstrated the usefulness of this system in diagnosing breast lesions among a cross section of the population , as well as, in specialized subsets of patients including males and patients having suspicious radiological breast lesions [24,25]. However, precise estimates of the sensitivity and specificity that collate the data, that is, a systematic review and meta-analysis of the diagnostic accuracy of breast FNAB using the IAC System, have not been performed.…”
Section: Introductionmentioning
confidence: 99%